A controlled antibiotic release system to prevent orthopedic-implant associated infections: An in vitro study - Gimeno, Marina (Eur J Pharm Biopharm, 2015)
A new device for local delivery of antibiotics is presented, with potential use as a drug-eluting fixation pin for orthopedic applications. The implant consists of a stainless steel hollow tubular reservoir packed with the desired antibiotic. Release takes place through several orifices previously drilled in the reservoir wall, a process that does not compromise the mechanical properties required for the implant. Depending on the antibiotic chosen and the number of orifices, the release profile can be tailored from a rapid release of the load (ca. 20 h) to a combination of rapid initial release and slower, sustained release for a longer period of time (ca. 200 h). An excellent bactericidal action is obtained, with 4-log reductions achieved in as little as 2 h, and total bacterial eradication in 8 h using 6-pinholed implants filled with cefazolin.